Reinforced concrete beams with web openings: A state of the art review - Ahmed A.; Fayyadh M.M.; Naganathan S.; Nasharuddin K. (2023)
The construction of modern buildings requires many pipes and ducts in order to accommodate essential services such as air conditioning, electricity, telephone, and computer network. Web openings in concrete beams enable the installation of these services. A number of studies have been conducted with regards to reinforced concrete beams which contain web openings. The present paper aims to compile this state of the art work on the behaviour, analysis and design of Reinforced Concrete (RC) beams with transverse web openings. A variety of aspects will be highlighted and discussed including the classification of openings, guidelines for opening location, and the structural behaviour of RC beams with web openings. Various design approaches will also be detailed, for example the American Concrete Institute (ACI) approach, the Architectural Institute of Japan (AIJ) approach and the strut and tie method. Moreover, the strengthening of RC beams with openings using Fibre Reinforced Polymer (FRP) material and steel plates is presented. Finally, directions for future research based on the gaps which exist in the present work are presented. 2012 Elsevier Ltd.